2007
DOI: 10.18553/jmcp.2007.13.4.326
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacoeconomic Analysis of Clopidogrel in Secondary Prevention of Coronary Artery Disease

Abstract: SUBJECT REVIEWBACkgrounD: When used as an alternative to or in addition to aspirin, clopidogrel has been demonstrated by some but not all randomized controlled trials to be effective in secondary prevention of cardiovascular (CV) events in patients with (1) coronary artery disease (CAD), (2) acute coronary syndrome (ACS), and (3) coronary stent placement. However, a drawback to clopidogrel therapy is the cost to patients and the health care system. Clinical studies have also demonstrated that when clopidogrel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Cheng [24] performed a pharmaco-economic analysis of clopidogrel in combination with aspirin and found it to be cost-effective up to 12 months after an MI, and our analysis indicated that it was valuable for at least that time after an MI.…”
Section: Discussionmentioning
confidence: 92%
“…Cheng [24] performed a pharmaco-economic analysis of clopidogrel in combination with aspirin and found it to be cost-effective up to 12 months after an MI, and our analysis indicated that it was valuable for at least that time after an MI.…”
Section: Discussionmentioning
confidence: 92%
“…Cheng 54 reviewed multiple cost-effectiveness studies on the use of clopidogrel for secondary prevention of cardiovascular events. She found that in all patients with NSTEMI and in those who received coronary stents, treatment with the drug was cost-effective when used in addition to ASA therapy for up to 12 months.…”
Section: Economic Analyses Of Cost-effectiveness Of Antiplatelet Thermentioning
confidence: 99%
“…She found that in all patients with NSTEMI and in those who received coronary stents, treatment with the drug was cost-effective when used in addition to ASA therapy for up to 12 months. 54 However, it was cost-effective when used for secondary prevention of coronary artery disease only in patients unable to tolerate ASA therapy. The studies she used in her analysis are included in Table 1.…”
Section: Economic Analyses Of Cost-effectiveness Of Antiplatelet Thermentioning
confidence: 99%
“…Meta-analyses of available pharmacoeconomic studies of clopidogrel suggest that dual antiplatelet therapy with clopidogrel and aspirin is cost-effective when used for up to 12 months in ACS patients and those undergoing PCI. 74,75 CONCLUSIONS A large body of evidence suggests that compared with aspirin alone, the addition of clopidogrel decreases the risk of death, recurrent MI, stroke, and the need for target vessel revascularization in ACS patients, although it does increase the risk of bleeding. Data from CRUSADE, GRACE, and ACTION show that despite its benefits, clopidogrel is underused in ACS patients, particularly those managed medically.…”
Section: Barriers To Dual Antiplatelet Therapymentioning
confidence: 99%